The Problem of Setting the Minimum Wage in Indonesia From The Perspective of Worker Protection - Dewi, Citra Kusuma; Kusuma, Emilia; Verdinand, Verdinand; PN , Sugeng Santoso (Jurnal Indonesia Sosial Sains, 2026)
The minimum wage policy is one of the important instruments in the labor law system in Indonesia that aims to provide protection to workers and ensure the fulfillment of a decent livelihood. However, in practice, the determination of the minimum wage still faces various problems that affect its effectiveness in improving the welfare of workers. This study aims to analyze the regulation and mechanism of setting minimum wages in Indonesia, as well as examine various problems that arise in its implementation from the perspective of worker protection. The research method used was normative legal research with a statutory approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials collected through literature studies and analyzed qualitatively. The results of the study show that normatively the regulation of the minimum wage has been regulated in various laws and regulations, and the determination mechanism involves the central government, local governments, and the Wage Council consisting of elements of the government, employers, labor unions, and academics. However, in practice, there are still various problems, such as the amount of the minimum wage that has not fully met the needs of a decent life, the difference in interests between workers and employers, and the influence of economic and investment policies on wage policies. Therefore, a more comprehensive and equitable wage policy is needed so that the determination of the minimum wage can function optimally as an instrument to protect workers while supporting sustainable economic development